Examining the Relationship Between TPACK Knowledge and Integration of Educational Technology Tools Among In-Service Chinese Language Teachers in Rural China - Wang, Lixia; Lee, Jun Choi; Ling, Chen (PEGEGOG, 2025)
This study examines the role of Technological Pedagogical Content Knowledge (TPACK) in Educational Technology (EdTech) integration among in-service Chinese language teachers in rural China. Using a cross-sectional survey of 506 teachers, findings indicate that Technological Pedagogical Knowledge (TPK) is the strongest predictor of EdTech adoption, significantly enhancing instructional efficacy and adaptability. Technological Knowledge (TK) and Technological Content Knowledge (TCK) also contribute, while Pedagogical Knowledge (PK) and Content Knowledge (CK) show minimal impact. The study highlights the need for TPK-focused professional development and cost-effective digital solutions to bridge rural resource gaps and promote equitable digital learning.